My Years with the Arabs ISF Monograph 8 - Glubb, John Bagot 1897-1986 (ISF Monographs, 2020)
For more than thirty years, The Institute for Cultural Research (ICR) led the field in stimulating debate and examining ideas within the humanities. Among the Institute's active followers was J. D. Salinger, Robert Graves, Nobel Laureate Doris Lessing, and many others from all walks of life.During its long and distinguished service, ICR published dozens of papers on cultural and cross-cultural themes. Written by scientists, scholars, novelists, musicians, and an array of others, these papers formed a unique resource that is as relevant today as it was decades ago.In the years since ICR ceased formal activities, The Idries Shah Foundation has continued the spirit of its work, and have republished the full range of original monographs.